Sixteen new species of the spider genus Althepus Thorell, 1898 (Araneae: Ochyroceratidae) from Southeast Asia - Li, Fengyuan; Liu, Chang; Wongprom, Prasit; Li, Shuqiang (Zootaxa, 2018)
Sixteen new Althepus species of the spider family Ochyroceratidae are reported from Southeast Asia: A. bamensis Li et Li sp. nov., A. changmao Li et Li sp. nov., A. dongnaiensis Li et Li sp. nov., A. guan Li et Li sp. nov., A. maechamensis Li et Li sp. nov., A. menglaensis Li et Li sp. nov., A. naphongensis Li et Li sp. nov., A. natmataungensis Li et Li sp. nov. (male only), A. phadaengensis Li et Li sp. nov., A. shanhu Li et Li sp. nov., A. suayaiensis Li et Li sp. nov. (male only), A. tadetuensis Li et Li sp. nov., A. tanhuang Li et Li sp. nov., A. thanlaensis Li et Li sp. nov., A. tharnlodensis Li et Li sp. nov. (female only), and A. viengkeoensis Li et Li sp. nov.